A modified mTNM staging system based on lymph node ratio for colon neuroendocrine tumors: A recursive partitioning analysis - Wang, Ye; Cai, Huajun; Zhang, Yiyi; Zhuang, Jinfu; Liu, Xing; Guan, Guoxian (Frontiers in Surgery, 2022)
Background: In the current tumor-lymph node-metastasis (TNM) staging system for colon NETs, lymph node status is divided into N1 and N0. An assessment of the lymph node ratio (LNR) and a proposal for a modified mTNM staging system were the objectives of this study. Methods: Selecting the optimal cutoff value of LNR by X-tile. A Cox regression model and the Kaplan-Meier method were performed to calculate patient cancer-specific survival (CSS) in SEER cohort. Recursive partitioning analysis (RPA) was used to improve TNM staging. Results: The study included 674 patients. The current TNM staging system showed inadequate discriminatory power between stage-I and stage-II patients (p=0.088). The optimal cut-off value was determined as 0.6 for LNR. Based on multivariate Cox regression analysis, the modified mN classification could be classified into mN 0 (LNR=0.00), mN 1 (LNR 0.01-0.60), and mN 2 (LNR >0.60), and was found to be an independent factor affecting prognosis (p<0.001). Using AJCC T and modified mN classifications, the modified mTNM system was constructed, and exhibited better prognostic discriminatory power ability than the traditional TNM system (C-index: 0.587 vs. 0.665). Conclusions: Our study determined that LNR is a prognostic factor in colon NET patients. In addition, to more accurately assess the prognosis of colon NET patients, we proposed a modified mTNM staging system.